Understanding the local context and its possible influences on shaping, implementing and running social accountability initiatives for maternal health services in rural Democratic Republic of the Congo: a contextual factor analysis. Issue 1 (December 2016) - Mafuta, Eric; Hogema, Lisanne; Mambu, Thérèse; Kiyimbi, Pontien; Indebe, Berthys; Kayembe, Patrick; De Cock Buning, Tjard; Dieleman, Marjolein
Abstract Background Social accountability has to be configured according to the context in which it operates. This paper aimed to identify local contextual factors in two health zones in the Democratic Republic of the Congo and discuss their possible influences on shaping, implementing and running social accountability initiatives. Methods Data on local socio-cultural characteristics, the governance context, and socio-economic conditions related to social accountability enabling factors were collected in the two health zones using semi-structured interviews and document reviews, and were analyzed using thematic analysis. Results The contexts of the two health zones were similar and characterized by the existence of several community groups, similarly structured and using similar decision-making processes. They were not involved in the health sector's activities and had no link with the health committee, even though they acknowledged its existence. They were not networked as they focused on their own activities and did not have enough capacity in terms of social mobilization or exerting pressure on public authorities or providers. Women were not perceived as marginalized as they often occupied other positions in the community besides carrying out domestic tasks and participated in community groups. However, they were still subject to the local male dominance culture, which restrains their involvement in decision-making, as they tend to be less educated, unemployed and suffer from a lack of resources or specific skills. The socio-economic context is characterized by subsistence activities and a low employment rate, which limits the community members' incomes and increases their dependence on external support. The governance context was characterized by imperfect implementation of political decentralization. Community groups advocating community rights are identified as "political" and are not welcomed. The community groups seemed not to be interested in the health center's information and had no access to media as it is non-existent. Conclusions The local contexts in the two health zones seemed not to be supportive of the operation of social accountability initiatives. However, they offer starting points for social accountability initiatives if better use is made of existing contextual factors, for instance by making community groups work together and improving their capacities in terms of knowledge and information.